Soy Juice Is Effective in Reducing Hot Flush Symptoms in Premenopausal Mothers - Ellyda Rizki Wijhati Wijhati; Sandiya Ferlina; Rosmita Nuzuliana (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Hot flush occurs in 73.3% of premenopausal mothers and is often accompanied by sleep disturbances and mood swings. This study aims to determine the effectiveness of soy juice in reducing hot flush symptoms in premenopausal mothers. This study uses a pre-experimental method with a type of one-group pretest-posttest design, and data analysis is carried out with the Wilcoxon Signed Ranks Test statistical test. The sampling technique used was purposive sampling with a total sample of 31 premenopausal mothers. The results showed that the consumption of soy juice reduced hot flush symptoms in premenopausal mothers with a significance value of 0.000 (ρ < 0.05). This shows that there is a significant influence before and after the administration of soy juice. The isofla-vones in soybean juice have a biological activity similar to estrogen and bind to estrogen receptors (Ers) as agonists. The reaction of the stimulation of the estrogen receptor Erα by isoflavones results in an interaction that affects the transcription process of cells, so that there is a stimulation of neurons in the central nervous system and resulting in a decrease in hot flush symptoms.